Exploring Psychological Factors Influencing Deliberation - Metka Kuhar (Interdisciplinary Description of Complex Systems, 2013)
In contemporary societies there is a growing need to coordinate and legitimize different perspectives. Instead of a dialogical search for consensus polarizing communication still prevails. The legitimacy of formal political institutions and conventional forms of political participation is in decline; increasingly publicly expressed people’s need for a greater influence on social developments reveals a deficit in approaches how to include them more actively in discussions on complex social problems. There has been a growing number of theoretical and empirical appeals to advance deliberation within governmental bodies and public institutions, as well as in a form of direct citizen involvement in (organized) face-to-face meetings. Yet, no radical shift has been made (so far), largely due to poor understanding of subjective and intersubjective (psychological) aspects of deliberation – the exploration of these aspects is the aim of this article. The case is being made for using till now unstudied influence of attachment style on the quality of deliberation and on the readiness to transform and coordinate attitudes with others in a deliberative process.